The discounted local limit theorems for large deviations - Saulis, Leonas; Deltuvienė, Dovilė (Lietuvos matematikos rinkinys, 2008)
Theorems of large deviations, both in the Cramer zone and the Linnik power zones, for the normal approximation of the distribution density function of normalized sum Sv = ∞ k=0 vkXk, 0 < v < 1, of i.i.d. random variables (r.v.) X0, X1, . . . satisfying the generalized Bernstein’s condition are obtained.